2019
DOI: 10.15698/mic2019.04.673
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-year evolution of probiotic therapy

Abstract: In the past forty-five years, the field of probiotics has grown from a handful of laboratory studies and clinical ideas into a legitimate research and translational entity conferring multiple benefits to humans around the world. This has been founded upon three principles: (i) the need for alterna-tives to drugs that either have sub-optimal efficacy or severe adverse effects; (ii) a growing interest in natural products and microbes, in particular cata-lyzed by studies showing the extent of microbes within huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 124 publications
0
21
0
3
Order By: Relevance
“…SDP supplementation had notable effects on probiotic species. The intestine houses numerous lactic acid-producing bacteria that promote health by producing metabolites that can interact with the host's own metabolism and immune system 41 . Most probiotics belonging to the genera Lactobacillus and Bifidobacterium modulate the GALT and prevent adhesion of and colonization by pathogens 42 .…”
Section: Discussionmentioning
confidence: 99%
“…SDP supplementation had notable effects on probiotic species. The intestine houses numerous lactic acid-producing bacteria that promote health by producing metabolites that can interact with the host's own metabolism and immune system 41 . Most probiotics belonging to the genera Lactobacillus and Bifidobacterium modulate the GALT and prevent adhesion of and colonization by pathogens 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that most of the information related to probiotic characterization is derived from in vitro cell culture studies or in vivo testing using models, and this information must be corroborated in order to use the results at an industrial scale [87,88]. In recent years, there was growing interest in the characterization of new LAB isolates from different sources to use them as probiotics or for other applications [89]. Yet, in parallel to isolation and characterization efforts, identification at a species level (and, in some cases, at a strain level) is necessary for commercial purposes.…”
Section: Probioticsmentioning
confidence: 99%
“…This concept has been further expanded to encompass prebiotics that stimulate the growth of beneficial gut bacteria ( Sarkar et al, 2016 ). Since probiotics modulate the host gut microbial communities and their synthesis/release of certain neuroactive compounds, probiotic-based therapy has thus been proposed as an alternative treatment for some neurological and neurodegenerative diseases ( Puebla-Barragan and Reid, 2019 ; Westfall et al, 2017 ). Recent clinical studies have shown that some probiotic strains could help relieve stress, anxiety, and depression symptoms ( Messaoudi et al, 2011 ; Takada et al, 2016 ), particularly, the Bifidobacterium ( B .)…”
Section: Introductionmentioning
confidence: 99%